Prevalence of Ear Nose and Throat (ENT) Manifestations Among HIV Seropositive Patients at a Tertiary Hospital in Northern Tanzania: A Descriptive Cross-Sectional Study - Shija PS (Dove Medical Press, 2020)
Peter Stephen Shija,1,2 Joshua Alexander Karaba,1,2 Rune Nathaniel Philemon,1,3 Bernard Lucas Minja,1 Philbert Patrick Mtenga,1,2 Denis Robert Katundu1,2 1Kilimanjaro Christian Medical Center Moshi (KCMC), Moshi, Tanzania; 2Department of Ear Nose and Throat (ENT) Head and Neck Surgery, Kilimanjaro Christian Medical University College (KCMUCo), Moshi, Tanzania; 3Kilimanjaro Christian Medical University College, Institute of Public Health Moshi, Moshi, TanzaniaCorrespondence: Peter Stephen ShijaDepartment of ENT Head and Neck Surgery, Kilimanjaro Christian Medical University College, P.O Box 2240, Moshi, TanzaniaTel +255754392916Email shijapsn@yahoo.comBackground: To date, HIV/AIDS remains a threat of the 21st century. The overall rate of new HIV infection continues to decline in several countries, but there is still a remarkable burden of disease seen in sub-Saharan Africa. Several studies observed that 70% to 90% of HIV-infected patients present with ear, nose and throat symptoms. The aim of this study was to identify the magnitude of ENT manifestations among HIV-infected patients attended HIV clinics at KCMC based on age, sex, and CD4 count.Methods: This was a descriptive cross-sectional study conducted at KCMC hospital involving HIV-infected patients who attended HIV clinics from February to July 2018. Convenient sampling was employed to get study participants, and 200 patients were recruited in the study. Data were collected through a questionnaire from patients, and results were analyzed using SPSS version 20.Results: Sixty-eight (34%) of 200 HIV-infected patients had ENT manifestations. The most affected age group was 0– 9 years. ENT manifestations were more prevalent in females (23.5%) than in males (10.5%). Those with CD4 count less than 200cells/μL also it was a high prevalence (56.3%).Conclusion: This study observed that one-third of the studied population had ENT manifestations. All medical practitioners should be aware of ENT manifestations in HIV-infected patients in order to assure early and appropriate intervention.Keywords: ENT manifestations, HIV, magnitude, seropositive, Tanzania